La nozione di autorità. Suggestioni da Alexandre Kojève - Chiara Ariano (Ius Humani. Jornal do direito, 2014)
Following the recent discovery of the volume by A. Koiève entitled The Notion of Authority – whose existence was previously known from a footnote in Esquisse d’une phénoménologie du droit – this article reviews the notion of authority using a phenomenological approach. The author starts from a conceptual analysis of the theories of authority by distinguishing 4 “simple‟ or “pure‟ categories (some analogues of the weberian types): – the theological or theocratic theory, according to which the only and primary authority belongs to God, all the others descending from it; – the Platonic theory, centred on Justice; – the Aristotelian theory, according to which the authority belongs to those who know and are able to foresee; – the Hegelian theory, which reduces the notion of authority to the relationship between sir and servant, thereby putting the emphasis on struggle and the recognition of a winner. According to Kojève, only the latter category “has received a complete philosophical elaboration, one that goes beyond a simple phenomenological description and uses metaphysical and ontological analyses.” However, the radical narrowness of man – on which Kojève basis its atheism and rejects the link between authority and transcendence – does not completely hides, according to the author of the article, traces of an anthropology where infinity appears again.